THE EVOLVING RIGHT TO EDUCATION IN THE AGE OF GENERATIVE AI 1 - BARIL, DANIEL (Revista Desenvolvimento & Civilização, 2026)
As the role of digital technology, and especially artificial intelligence, becomes increasingly widespread and normalized in education, it is important to reflect on how technology is reshaping learning across the life course. My purpose is to connect concrete practice—the tools and platforms already in classrooms, communities, and workplaces—with a policy agenda grounded in the right to education. The global UNESCO policy goal remains the same: to ensure equitable access to high-quality learning opportunities for all, at all stages of life. To achieve this goal, we must now examine the ongoing technological transformation of education, particularly in relation to the evolving right to education in the age of generative artificial intelligence.